Machining-induced grain refinement of AISI 4340 alloy steel under dry and cryogenic conditions - A. Raof, Natasha; A. Ghani, Jaharah; Che Haron, Che Hassan (Elsevier, 2019)
Machining significantly influences surface integrity, metallurgical structure, grain size and thereby the mechanical, chemical and physical properties of the component. The presented investigation concentrates on grain refinement in turning of AISI 4340 alloy steel in dry and cryogenic turning. With cutting temperatures below 950 ◦C, the resulted surface layer consists of a microstructure with ultrafine white globular particles in all samples. A higher percentage of these particles was observed when using cryogenic flushing. It resulted in improved surface and subsurface properties in terms of ultrafine microstructure concentration, higher micro hardness, influence on the thickness and composition of the surface, and subsurface layers and thermal stability